New psychoactive substances: towards a conceptual delimitation - Henriques, S.; Guerreiro, M. D.; Silva, J. (Análise Social, 2019)
New Psychoactive Substances (nps) are a relatively recent phenomenon characterized by continuous expansion throughout more or less the entire world in the last decade. They include a diversity of natural or synthetic substances that are not yet on official lists and whose great variety and rapid transformations make the nps concept itself hard to define. Methodologically combining qualitative methods in order to present a problematized systematization of national and public policies, and quantitative ones presenting the results of a survey applied to users of nps in Portugal, the paper contributes to a more precise definition of nps and their effects and to know about the evolution of the applicable legal framework.